Advances on material science and manufacturing technologies - Xu, Qingzhou (Advanced materials research, 2013)
The collection includes selected, peer-reviewed papers from the International Conference on Materials Science and Manufacturing (ICMSM2012) held December 14-16, 2012 in Zhangjia Jie, China. It aims to cover the recent advancement and trends in the area of new materials, advanced materials, advanced manufacturing technologies, and manufacturing systems and automation to facilitate knowledge sharing and networking interactions on emerging trends and new challenges.